2014
DOI: 10.2196/jmir.2990
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Guided Self-Help Exercise Program to Prevent Speech, Swallowing, and Shoulder Problems Among Head and Neck Cancer Patients: A Feasibility Study

Abstract: BackgroundDuring a 6-week course of (chemo)radiation many head and neck cancer patients have to endure radiotherapy-induced toxicity, negatively affecting patients’ quality of life. Pretreatment counseling combined with self-help exercises could be provided to inform patients and possibly prevent them from having speech, swallowing, and shoulder problems during and after treatment.ObjectiveOur goal was to investigate the feasibility of a multimodal guided self-help exercise program entitled Head Matters during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
64
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 64 publications
0
64
1
2
Order By: Relevance
“…(31, 32) One study(27) did not report an age range or mean. Including all studies that reported the age range and mean,(2426, 2830, 33) the collective age range for this review was 21–94, and the mean was 60.4 years.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…(31, 32) One study(27) did not report an age range or mean. Including all studies that reported the age range and mean,(2426, 2830, 33) the collective age range for this review was 21–94, and the mean was 60.4 years.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies(17, 25, 27, 34) completed retrospective studies earning a JAMA score of 3. Five studies(24, 26, 28, 30, 33) earned a JAMA quality rating score of 4 and used the following designs: prospective cohort,(24) case-series(26, 28, 33) and pilot study. (30)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations